Psychosocial and Motor Characteristics of Patients With Hypermobility - Lamari, Mateus M.; Lamari, Neuseli M.; Araujo-Filho, Gerardo M.; Medeiros, Michael P.; Pugliesi Marques, Vitor R.; Pavarino, Érika C. (Frontiers in Psychiatry, 2022)
Objectives To identify psychosocial and motor aspects related to joint hypermobility (JH) in a sample from almost all Brazilian states by age range and sex; to characterize JH by the Beighton total score ≥4, ≥5, and ≥6 according to sex and age and atypicality in the sitting position and in the hands; identify, in the total sample, manifestations of “growing pain” and its location, fatigue, attention deficit, anxiety, insomnia, drowsiness, apathy, depression, delay in walking, not crawling or crawling differently, school performance, spatial orientation and/or temporally impaired, social isolation, and being stigmatized as “lazy/clumsy/apathetic”. Methods This retrospective, observational, quantitative, and cross-sectional study used data obtained through analyses of descriptive and inferential crossings between 2012 and 2020 of 482 medical records of individuals between 1 and 76 years of age, from most Brazilian states. All patients previously diagnosed with “joint hypermobility syndrome” (JHS) and “Ehlers-Danlos syndrome hypermobility type” (EDS-HT) had their medical records reassessed, following the guidelines established in 2017. The analysis of GJH was performed using the updated method by Beighton method; atypical characteristics were investigated in the hands and the ability to sit in the “W” and the “concave” positions. The characteristics and manifestations of “growing pain” and its location were analyzed in the total sample, fatigue, insomnia, drowsiness, apathy, depression, social isolation, attention deficit, anxiety, stigmatization as “lazy,” clumsy/restless, impaired school performance, and spatial and/or temporal orientation. Descriptive and inferential statistical methods were used, such as Mean, Median, Mode, Standard Deviation, Standard Error, Maximum Value, Minimum Value, Komolgorov-Smirnov, Significance, Relative Value, Absolute Value, Mann-Whitney U, and Correlation of Spearman. Results JH in the total sample predominated in the upper limbs, the majority were women, represented by 352 (73.02%), 15 years old or older with 322 (66.80%), 312 (64.73%) had a Beighton total score ≥6, which decreased as the age increased. Always sitting in the “concave” position was represented by 54.15% and the ability to sit in the “W” position by 39.21%; signs on the hands totaled between 27.59 and 44.19% with a significant correlation between the variables. Among the characteristics, fatigue predominated, followed by an awkward/clumsy/restless individual, attention deficit, anxiety and stigmatized as “lazy,” insomnia, drowsiness, apathy, depression, impaired spatial and/or temporal orientation, and social isolation. From the total sample, pain in the lower limbs was reported by 55.81% and having or having had “growing pain” was reported by 36.93%, delay in walking occurred in 19.92%, 15.35% did not crawl or crawled differently, and for 12.86%, school performance was impaired. Higher Beighton total scores showed a trend towards motor implications and correlation between variables. Ability to still sit in the “concave” position was possible for 54.15% and to sit in the “W” position for 39.21%. Conclusion In the total sample, the JH characteristic prevails in the upper limbs of female children, adolescents and adults, with a total Beighton score ≥6. Most sit in the “concave” position and less than half also sit in the “W” position and with atypical hand postures. The higher Beighton scores, which include the upper limbs, show a tendency to not crawl or crawl differently, delayed ambulation, and impaired school performance. The predominance of JH in the upper limbs is suggestive of a justification for not crawling or crawling differently. Characteristics of atypical motor performance in hands and sitting posture, in addition to fatigue, pain since childhood, anxiety, apathy, depression, sleep disorders, stigmatization, attention deficit, spatial and/or temporal orientation impairment, and social isolation are characteristics. suggestive of psychosocial implications at different ages. Future studies with motor and psychosocial aspects of people with JH will help to identify the phenotype of this population and consequent guidance for clinical management based on the motor and psychosocial aspects of people with JH.